Determination of the Initial Abnormal Discharge Site in Temporal Lobe Epilepsy Through Combined EEG and Neuroimaging. What Is Next? - Rentería-Palomo, Ana A.; Montes-Ochoa, Jose L.; Martinez-Mayorga, Adriana; Reyes-Vaca, Jorge Guillermo; Rodríguez-Leyva, Ildefonso (Frontiers in Neurology, 2021)
Objective: The objective of this study was to determine the relationship between atrophy of the hippocampus and severity of epilepsy in patients with temporal lobe epilepsy (TLE) as the first step to evaluate the possibility of surgery for epilepsy and analyze why patients cannot undergo epilepsy surgery. Methods: Volumetric MRI of the hippocampus was performed in 51 consecutive patients (29 men; mean age 40) with TLE. TLE diagnosis, lateralization, and severity (mild, moderate, severe) of seizures were based on a comprehensive evaluation that included neurologic examination and EEG in all patients. Patients with evidence of a lesion other than hippocampal sclerosis were not included in the study. We assessed the relationship between hippocampal volumes and electrophysiological evidence of seizure severity. Results: According to the affected side based on the EEG, a statistically significant difference (p < 0.001) in volume and a positive correlation between epilepsy and hippocampal atrophy were found. Conclusion: Our results confirm that volume loss to the hippocampus in patients with TLE correlates with the severity of epilepsy based on the EEG. Therefore, surgical treatment is considered early when hippocampal atrophy is evident in patients with refractory TLE. However, in Latin American countries, it is a challenge to get a patient to undergo epilepsy surgery. Therefore, we try to analyze the sad situation in our hospital.